Volume 3: Heat Transfer; Electric Power; Industrial and Cogeneration 1997
DOI: 10.1115/97-gt-326
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Experimental Investigations of Straight-Through Labyrinth Seals

Abstract: Computational and experimental investigations are carried out to estimate leakage flow rate in a static straight-through labyrinth seal. Tests were conducted over a range of pressure ratios, varying from 1.003 to 1.897, for three clearance values of 0.2, 0.36 and 0.6 mm respectively. The measured values of leakage flow parameter are corroborated with the results obtained from the simulations using FLUENT computer package. The agreement was within 8.6%. The flow details, e.g., the stream line pattern, velocity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In the calculation of labyrinth leakage flow, the accuracy of CAM is validated by the data of Prasad [35]. Prasad et al tested the straight-through labyrinth shown in Figure 2, and obtained the flow characteristics of the labyrinth under 12 working conditions (pressure ratio from 1.0031 to 1.8974).…”
Section: Numerical Model and Research Objectmentioning
confidence: 98%
See 3 more Smart Citations
“…In the calculation of labyrinth leakage flow, the accuracy of CAM is validated by the data of Prasad [35]. Prasad et al tested the straight-through labyrinth shown in Figure 2, and obtained the flow characteristics of the labyrinth under 12 working conditions (pressure ratio from 1.0031 to 1.8974).…”
Section: Numerical Model and Research Objectmentioning
confidence: 98%
“…In the calculation of labyrinth leakage flow, the accuracy of CAM is validated by the data of Prasad [35]. Prasad et al tested the straight-through labyrinth shown in Figure 2, and obtained the flow characteristics of the labyrinth under 12 working conditions (pres- Considering the advantages of the two-dimensional method in the simulation of full-aeroengine and the non-negligible influence of the seal cavity leakage flow on the performance of turbomachinery, we have reason to believe that a two-dimensional throughflow program considering seal cavity leakage flow can undoubtedly assist in the performance prediction of an aeroengine.…”
Section: Numerical Model and Research Objectmentioning
confidence: 99%
See 2 more Smart Citations
“…They also presented the traditional rotordynamic model used for predicting the reaction force components of an annular gas seal. Prasad et al [8][9][10] had performed both experimental and numerical investigations of different labyrinth configurations, namely, straight-through, inclined and radial labyrinth seals. Kim and Cha [11] presented a comparative analysis of the influence of configuration and clearance on the leakage behavior of labyrinth seals using CFD and reported leakage flow pattern for various clearances.…”
Section: Introductionmentioning
confidence: 99%